The Thousand and One Nights: Sources and Transformations in Literature, Art, and Science - Granara, William,; Akel, Ibrahim, (Studies on Performing Arts & Literature of the Islamicate World ;, 2020)
The Thousand and One Nights does not fall into a scholarly canon or into the category of popular literature. It takes its place within a middle literature that circulated widely in medieval times. The Nights gradually entered world literature through the great novels of the day and through music, cinema and other art forms. Material inspired by the Nights has continued to emerge from many different countries, periods, disciplines and languages, and the scope of the Nights has continued to widen, making the collection a universal work from every point of view. The essays in this volume scrutinize the expanse of sources for this monumental work of Arabic literature and follow the trajectory of the Nights ' texts, the creative, scholarly commentaries, artistic encounters and relations to science. Contributors: Ibrahim Akel, Rasoul Aliakbari, Daniel Behar, Aboubakr Chraïbi, Anne E. Duggan, William Granara, Rafika Hammoudi, Dominique Jullien, Abdelfattah Kilito, Magdalena Kubarek, Michael James Lundell, Ulrich Marzolph, Adam Mestyan, Eyüp Özveren, Marina Paino, Daniela Potenza, Arafat Abdur Razzaque, Ahmed Saidy, Johannes Thomann and Ilaria Vitali.